1990
DOI: 10.1210/endo-126-5-2768
|View full text |Cite
|
Sign up to set email alerts
|

The Rat Follistatin Gene is Highly Expressed in Decidual Tissue

Abstract: Follistatin was originally described as an ovarian polypeptide hormone able to suppress pituitary follicle-stimulating hormone (FSH) secretion in in vitro systems. We have isolated rat ovarian follistatin cDNA clones and used these to investigate the possibility that decidual tissue expresses the follistatin gene. We found that the follistatin gene is highly expressed during early pregnancy in tissue derived from the site of blastocyst implantation. Follistatin mRNA was observed in tissue obtained from the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 1 publication
6
28
1
Order By: Relevance
“…Similar effects offollistatin have been demonstrated on ovariectomized rats in vivo ( 17 ). Follistatin mRNA has been detected in a wide variety ofextragonadal tissues, including the kidney, cerebral cortex, and decidual tissue (18)(19)(20). In addition, we and others have detected follistatin mRNA in the rat pituitary (20)(21)(22)(23).…”
Section: Introductionsupporting
confidence: 79%
“…Similar effects offollistatin have been demonstrated on ovariectomized rats in vivo ( 17 ). Follistatin mRNA has been detected in a wide variety ofextragonadal tissues, including the kidney, cerebral cortex, and decidual tissue (18)(19)(20). In addition, we and others have detected follistatin mRNA in the rat pituitary (20)(21)(22)(23).…”
Section: Introductionsupporting
confidence: 79%
“…Compared to the SRC-2 flox/flox positive control, real-time PCR revealed a significant reduction in the expression levels of a number of decidualization markers (18,22,49) in the partially decidualized PR Cre/ϩ SRC-2 flox/flox uterine horn (Fig. 5).…”
Section: The Absence Of Implantation Sites In the Prmentioning
confidence: 96%
“…decidualization, those for bone morphogenetic protein 2 (Bmp-2) (49), cyclooxygenase 2 (Cox-2) (22), and follistatin (18), were validated by real-time RT-PCR TaqMan analysis with the ABI Prism 7700 Sequence Detector System according to the manufacturer's instructions (PE Applied Biosystems, Foster City, CA). The TaqMan gene expression assay (catalog no.…”
Section: Generation Of Prmentioning
confidence: 99%
“…The general principle to emerge from this work is that the early stages of implantation and decidualization are characterized by the spatiotemporal pattern of expression of the mRNAs encoding several members of the BMP family. These include BMP-2 in the decidualizing stromal cells (Ying & Zhao 2000, Paria et al 2001, BMP-4 and Smad1 in vascular endothelial cells (Ying & Zhao 2000), BMP-7 in the endothelium and subjacent stroma (Ozkaynak et al 1997, Paria et al 2001, BMP-8a in decidual cells (Zhao & Hogan 1996), BMP-RIB in the endometrium and endometrial glands (Yi et al 2000), follistatin in decidual tissue (Kaiser et al 1990, Mercado et al 1993) and noggin and DAN in the stromal layer immediately underlying the luminal endothelium (Paria et al 2001). This evidence has suggested that BMPs in the uterus have a potential role in pregnancy.…”
Section: Introductionmentioning
confidence: 99%